A theorem on maximizing the probability of correct integer estimation. - Teunissen, Peter (1999)
High ambiguity success rates are required for GPS ambiguity resolution to be successful. It is therefore of importance to be able to identify the integer estimators which maximize these success rates. In this contribution we present a theorem which shows when the success rate is maximized. This theorem generalizes a result of (Teunissen, 1998), which states that, in case of elliptically contoured distributions, it is the integer least-squares estimator that provides the largest probability of correct integer estimation.